2018
DOI: 10.3390/ijerph15091935
|View full text |Cite
|
Sign up to set email alerts
|

Does Information Pattern Affect Risk Perception of Food Safety? A National Survey in China

Abstract: Examining the variances in the assessments of risk, as perceived by residents, facilitates the development of appropriate risk information communication strategies. This paper aims to identify the effects of information source patterns on perceived food safety risks based on demographic factors. A national survey was conducted to examine, by means of multiple regression analysis, the relationship between the public’s perceived risks, demographic factors and information access. The study finds that residents’ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 31 publications
4
20
0
1
Order By: Relevance
“…This finding validates that government performance and economic interests promote governmental trust. Economic growth is not only about the increase and expansion of wealth but also reflects the growth of people’s actual welfare and the improvement of their quality of life [35]. Meanwhile, the sustainability of economic growth depends on the transformation and optimization of the economic structure, where the government plays an important role in controlling the overall economic trends, economic regulation and the optimization of resource allocation.…”
Section: Discussionmentioning
confidence: 99%
“…This finding validates that government performance and economic interests promote governmental trust. Economic growth is not only about the increase and expansion of wealth but also reflects the growth of people’s actual welfare and the improvement of their quality of life [35]. Meanwhile, the sustainability of economic growth depends on the transformation and optimization of the economic structure, where the government plays an important role in controlling the overall economic trends, economic regulation and the optimization of resource allocation.…”
Section: Discussionmentioning
confidence: 99%
“…Food safety concerns in China are still severe, and China is still facing threats and challenges from many food safety risk factors [3]. Food safety is still one of the extremely serious issues of public concern in China and the public perceive lots of food safety risk and anxieties [6].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have found that perceptions of food safety risk are closely linked with socioeconomic status and demographic characteristics [ 20 ]. Thus, some studies have focused on the relationship between demographic factors and perceptions of food safety [ 21 ] and the influences of socioeconomic factors on respondents’ perceptions of food safety [ 22 , 23 , 24 , 25 , 26 ]. Some studies observed the influences of demographic factors (e.g., gender, age, educational level, income, marriage) and socioeconomic factors (e.g., consumers’ knowledge of policy, media exposure, information pattern, state employment) based on data from different countries or regions.…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%